Employment Discrimination against Indigenous Peoples in the United States: Evidence from a Field Experiment - Patrick Button; Brigham Walker (Institute of Labor Economics (IZA), 2019)
We conducted a resume correspondence experiment to measure discrimination in hiring faced by Indigenous Peoples in the United States (Native Americans, Alaska Natives, and Native Hawaiians). We sent employers realistic resumes for common jobs (retail sales, kitchen staff, server, janitor, and security) in 11 cities and compared interview offer rates. We signaled Indigenous status in one of four different ways. Based on 13,516 applications, we do not find hiring discrimination in any context. These findings hold after numerous robustness checks, although our checks and discussions raise multiple concerns that are relevant to audit studies generally.
Keywords: J15; J7; C93; 330; indigenous peoples; employment discrimination; Native American; Alaska Native; Native Hawaiian; Indian reservations; correspondence experiment; resume study; Oaxaca-Blinder Decomposition